Revamping Real Estate Taxation in Pakistan: Prospects and Challenges - Dr Mahak Mansoor (`, 2025)
This research paper aims to study, describe and analyze challenges faced in effective real estate taxation in Pakistan and reforms in this sector since 2017. It studies its progress in the province of Punjab. It substantiates the validity of such reforms by comparison of Pakistan to other countries. It elaborates their role in the documentation of the tax base. It will provide administrative and legal recommendations to counter its shortfalls. Keywords: real estate taxation, Pakistan